Metadiscourse in the Kenyan CEO Letter Genre: A Corpus-Assisted Study - Wangari, Stella; Maroko, Geoffrey Mokua (Language Circle: Journal of Language and Literature, 2023)
Metadiscourse denotes the writer’s use of language to enhance interaction with the reader. This article investigates the use of language to persuade readers and represent the company positively. The study examines the use of Metadiscourse resources in CEO letters of financial service companies listed in the Nairobi Securities Exchange. A total of 36 companies were sampled to represent companies that offer insurance, investment and banking services. The study utilized text analysis software (AntConc 3.5.7) to determine the quantitative outline of the Metadiscourse devices. This was followed-up with a qualitative analysis of the context in which the devices were applied, for further interpretation of the findings. All devices in the metadiscourse model were found in the text with a notably high incidence of self-mentions and transitions. This was attributed to the need to create reader-participation as well as to ease reader navigation through the text.  The findings are expected to further explain the role of Metadiscourse in financial disclosure by elaborating on its rhetorical nature. Results also highlight the importance of Metadiscourse features in the interpretation of content and attainment of diverse professional goals. Keywords: Interactional Metadiscourse, Interactive Metadiscourse, Genre, CEO Letter, Rhetoric